Injectable magnetic supramolecular hydrogel with magnetocaloric liquid-conformal property prevents post-operative recurrence in a breast cancer model. (1st July 2018) - Wu, Haoan; Song, Lina; Chen, Ling; Zhang, Wei; Chen, Yi; Zang, Fengchao; Chen, Hong; Ma, Ming; Gu, Ning; Zhang, Yu
Graphical abstract: Abstract: Locoregional recurrence of breast cancer after tumor resection represents several clinical challenges. Here, we demonstrate that co-delivery of chemotherapy and thermotherapeutic agents by a magnetic supramolecular hydrogel (MSH) following tumor resection prevents tumor recurrence in a breast cancer mouse model. The self-assembled MSH was designed through the partial inclusion complexation associated with the threading of α-CD on the copolymer moieties on the surface of the PEGylated iron oxide (Fe3 O4 ) nanoparticles, which enables shear-thinning injection and controllable thermoreversible gel-sol transition. MSH was injected to the postoperative wound uniformly, which became mobile and perfect match with irregular cavity without blind angle due to the magnetocaloric gel-sol transition when exposed to alternating current magnetic field (ACMF). The magnetic nanoparticle-mediated induction heat during the gel-sol transition process caused the triggered release of dual-encapsulated chemotherapeutic drugs and provided an effect of thermally induced cell damage. The hierarchical structure of the MSH ensured that both hydrophobic and hydrophilic drugs can be loaded and consecutively delivered with different release curves. The hydrogel nanocomposite might provide a potential locally therapeutic approach for the precise treatment of locoregional recurrence of cancer. Statement of Significance: Tumor recurrence after resection represents several clinical challenges. In this study, we prepared shear-thinning injectable magnetic supramolecular hydrogel (MSH) and demonstrated their therapeutic applications in preventing the post-operative recurrence of breast cancer with facile synthesis and minimally invasive implantation in vivo. MSH was injected to the postoperative wound uniformly, which become mobile and perfect match with irregular cavity without blind angle through magnetocaloric gel-sol transition when exposed to ACMF. The magnetic nanoparticles mediated induction heat during the gel-sol transition process caused the triggered release of dual-encapsulated chemotherapeutic drugs as well as thermally induced cell damage. This study demonstrates that MSH with the controlled administration of combined thermo-chemotherapy exhibit great superiority in terms of preventing post-operation cancer relapse.